2002
DOI: 10.1200/jco.2002.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes From an Institutional Series of Acinar Cell Carcinoma of the Pancreas and Related Tumors

Abstract: The survival curves suggest a more aggressive cancer than pancreatic endocrine neoplasms but one that is less aggressive than ductal adenocarcinoma of the pancreas. Those patients who present with localized disease have a much better prognosis than those who present with metastases. There is a high recurrence rate after complete surgical resection, suggesting that micrometastases are present even in localized disease and that adjuvant therapies may be indicated. Chemotherapy and radiation afford disappointing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
300
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(310 citation statements)
references
References 18 publications
8
300
0
2
Order By: Relevance
“…The distinction between acinar cell carcinoma and pancreatic neuroendocrine tumors is important clinically as acinar cell carcinomas typically have a poor prognosis. 42 Histologically, acinar cell carcinomas and well-differentiated neuroendocrine tumors can be virtually indistinguishable, and the differentiation between these two entities often requires immunohistochemical analysis. Chymotrypsin and trypsin are relatively sensitive immunohistochemical markers of acinar differentiation, 43 but a significant subset of pancreatic neuroendocrine tumors can focally express these markers.…”
Section: Pax8 Expression In Neuroendocrine Tumorsmentioning
confidence: 99%
“…The distinction between acinar cell carcinoma and pancreatic neuroendocrine tumors is important clinically as acinar cell carcinomas typically have a poor prognosis. 42 Histologically, acinar cell carcinomas and well-differentiated neuroendocrine tumors can be virtually indistinguishable, and the differentiation between these two entities often requires immunohistochemical analysis. Chymotrypsin and trypsin are relatively sensitive immunohistochemical markers of acinar differentiation, 43 but a significant subset of pancreatic neuroendocrine tumors can focally express these markers.…”
Section: Pax8 Expression In Neuroendocrine Tumorsmentioning
confidence: 99%
“…However, the knowledge of the efficiency of any neoadjuvant or adjuvant with radiation or chemotherapy for acinar cell carcinomas is limited as less data are available regarding the efficacy of systemic therapy in the management of these carcinomas, with the published experience to date limited to small case series or case reports. One of the largest single-institution study was published from the Memorial Sloan Kettering cancer centre in 2002 [5]; at that time, the reported experience with systemic chemotherapy for ACC was not promising and concluded that the high recurrence rate of acinar cell carcinoma indicated that micrometastasis are likely present at the time of surgery, making adjuvant therapy necessary. Acinar cell carcinomas are moderately chemoresponsive to agents that have activity in pancreatic adenocarcinoma and colorectal carcinoma.…”
Section: Treatmentmentioning
confidence: 99%
“…Approximately 10-15 % of patients develop lipase hypersecretion syndrome, in which massive quantities of lipase are released by the neoplasm into the bloodstream with levels reaching over 10,000 U/dl, with clinical symptoms including multiple nodular foci of subcutaneous fat necrosis and polyarthralgia due to sclerotic lesions in cancellous bone because of fat necrosis in the bone [5,6]. Peripheral blood eosinophilia and parathyropathies also occur.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations